2021
DOI: 10.20452/pamw.15946
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus disease 2019 (COVID-19) among hospitalized patients in Poland: a study based on a national hospital registry

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution-NonCommercial-ShareAlike 4.0 International License (CC BY-NC-SA 4.0), allowing third parties to copy and redistribute the material in any medium or format and to remix, transform, and build upon the material, provided the original work is properly cited, distributed under the same license, and used for noncommercial purposes only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 26 publications
(37 reference statements)
0
13
0
Order By: Relevance
“…Both patient-related and systemic factors might be responsible for this phenomenon. Pandemicspecific protocols for preparing personal protective equipment and obligatory COVID-19 testing consume additional time and extend the time for reperfusion [1][2][3][4]10,12]. Most previous studies have suggested longer total ischemia time and time from first medical contact do angiography in patients admitted during COVID-19 pandemic [1,25,29].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Both patient-related and systemic factors might be responsible for this phenomenon. Pandemicspecific protocols for preparing personal protective equipment and obligatory COVID-19 testing consume additional time and extend the time for reperfusion [1][2][3][4]10,12]. Most previous studies have suggested longer total ischemia time and time from first medical contact do angiography in patients admitted during COVID-19 pandemic [1,25,29].…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic negatively affected access to healthcare system and timeline of treatment [1][2][3][4]. The distribution of medical attention and resources with inevitable delays in treatment related to mandatory infection control might have a detrimental impact on outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Poland introduced extensive anti-epidemic measures relatively early, in order to slow down the spread of the disease. Already on 2 March 2020, i.e., earlier than the first case of COVID-19 infection in Poland, a Crisis act was introduced, that is, a Law on special arrangements for the prevention of and fight against COVID-19 [16,17]. In Poland, there were three waves of the pandemic-the first one in spring 2020, the second one in autumn 2020, the third one in spring 2021.…”
Section: Discussionmentioning
confidence: 99%